Commodity Transport Studies JUTE Joint Technical Group for Transport Planning - Planning Commission (Planning Commission, 1967)
Jute occupies an important place in the Indian economy. The jute industry earns for the country about 20% of its total foreign exchange earnings. Two lakh workers are employed in the Jute industry, and another 2 million agricultural families are dependent upon the /cultivation and marketing of jute. 1.2 Jute is a rainy season crop, sown from March' to May and harvested from June to September Mesta is coarser and more brittle, and is used by the jute mills for mixing with jute, Jute and mesta thrive best in the climatic conditions prevailing in West Bengal^ East Bengal and North Bihar.
Commodity Transport Studies